PENGARUH PERSEPSI MANFAAT DAN PERSEPSI RISIKO TERHADAP KEPUTUSAN PENGGUNAAN KARTU KREDIT BANK BCA - Gustiany, Muhammad Ammyl; Wiwaha, Arjuna (E-Journal Widya Ekonomika, 2020)
BCA was established on February 21, 1957 in the commercial center of Jakarta under the name "Bank Central Asia, N. V.". After going public in 2002, BCA is now known as "PT Bank Central Asia, Tbk". Vision of BCA to be the bank of choice for the public, which plays an important role in the Indonesian economy. This study discusses the effect of perceived benefits and risk perceptions on purchasing decisions. The purpose of this study was to determine the effect of perceived benefits and risk perceptions on decisions to use BCA bank credit cards. This research was conducted at PT BCA Tbk KCP Roxy Mas, Central Jakarta. When the research was carried out from February to July 2020, this research used literary methods and field methods. The number of samples in this study amounted to 89 customers. This study was processed using SPSS 25. The results of the study concluded that 26.7% of the decision to purchase using a BCA bank credit card was influenced by perceived benefits and risk perceptions.